Lessons for a learning health system: Effectively communicating to patients about research with their health information and biospecimens - Kayte Spector‐Bagdady; Kerry A. Ryan; Luyun Chen; Camille Giacobone; Reshma Jagsi; Reema Hamasha; Katherine Hendy; J. Denard Thomas; Jessie M. Milne; Alexandra H. Vinson; Jodyn Platt (Learning Health Systems)
Abstract Introduction Sharing patient health information and biospecimens can improve health outcomes and accelerate breakthroughs in medical research. But patients generally lack understanding of how their clinical data and biospecimens are used or commercialized for research. In this mixed methods project, we assessed the impact of communication materials on patient understanding, attitudes, and perceptions. Methods Michigan Medicine patients were recruited for a survey (n = 480) or focus group (n = 33) via a web‐based research study portal. The survey assessed the impact of mode of communication about health data and biospecimen sharing (via an informational poster vs. a news article) on patient perceptions of privacy, transparency, comfort, respect, and trust. Focus groups provided in‐depth qualitative feedback on three communication materials, including a poster, FAQ webpage, and a consent form excerpt. Results Among survey respondents, the type of intervention (poster vs. news) made no statistically significant difference in its influence on any characteristic. However, 95% preferred that Michigan Medicine tell them about patient data and biospecimen research sharing versus hearing it from the news. Focus group participants provided additional insights, discussing values and perceptions of altruism and reciprocity, concerns about commercialization, privacy, and security; and the desire for consent, control, and transparency. Conclusion Developing our understanding of patient data‐sharing practices and integrating patient preferences into health system policy, through this work and continued exploration, contributes to building infrastructure that can be used to support the development of a learning health system across hospital systems nationally.